DIFFERENCES IN ILLNESS PERCEPTIONS BETWEEN PARTICIPANTS WITH MILD COGNITIVE IMPAIRMENT AND THEIR CARE PARTNERS. (16th November 2018) - Mattos, M; Sereika, S; Kim, H; Tamres, L; Knox, M; Lingler, J
Abstract: At diagnosis, persons with mild cognitive impairment (PwMCI) and their care partners can receive information that can lead individuals to over or underestimate the significance of MCI as a potential precursor to dementia. Understanding how PwMCI and their care partners perceive the illness can help guide these challenging discussions. The purpose of this secondary analysis was to compare illness perceptions (IPs) between PwMCI and their care partners. This cross-sectional study examined baseline illness perceptions between PwMCI and care partners participating in an RCT examining the impact of disclosing amyloid PET results. IPs were measured by the Brief Illness Perception Questionnaire (B-IPQ). Repeated measures ANOVA/MANOVA was performed to examine within-dyad differences. Sixty-eight dyads were comprised of mostly male PwMCI (62.7%) and female care partners (77.9%). PwMCI tended to be older and more educated than their care partner (ps=.001). Overall B-IPQ scores differed across PwMCI and care partner (Mean=54.12 vs. 50.10, p=.039). When the set of B-IPQ dimensions were examined multivariately across PwMCI and their care partners, PwMCI's IPs were different than care partner's IPs (p<.001). Examination of the eight individual dimensions revealed only a difference in control, where PwMCI perceived MCI to be more within their personal control (Mean=5.73) than their care partner (Mean=2.86, p<.001). PwMCI perceive a more threatening view of MCI, however, with a greater sense of control than their care partners. Interventions encouraging dyads to explore differing perceptions of MCI may promote shared decision making, planning ahead, and, ultimately, improve dyadic well-being.